Mari Berbicara Dengan Bahasa Yang Benar Dan Etis di Ruang Digital Untuk Siswa SMA Laboratorium UPGRIS Semarang - Triani Triani; Nurdhiana Nurdhiana; Tantri Widiastuti; Tjandra Tirtono (BADAN PENERBIT STIEPARI PRESS, 2024)
This community service aims to provide discourse and provide an understanding of the importance of speaking correctly and ethically in the digital space. This is important because the increasing development of technology in the digital era has resulted in new breakthroughs in social media and the like. Social Media (digital media) is a means of communication for the world community that relatively closes the distance between one region and another, which makes it very easy for users to interact with anyone, so correct and ethical language procedures are needed when communicating in the digital space. A language is considered correct if it is a mixture of six types of digital language (EYD Indonesian, mass media language, social media, digital community, emojis, and machine language), masters digital literacy, is polite, does not violate the law, and gives kindness. Meanwhile, language politeness, which is called language etiquette or language ethics, is basically the speaker's attitude towards the interlocutor which is manifested in the use of language. The essence of language or speaking is respect for oneself, other people, differences of opinion, values and norms, multiculturalism and pluralism